Gender and the changing face of Higher Education in Asia Pacific - Abbas, Andrea (Critical Studies in Teaching and Learning, 2023)
Book Review: Neubauer, D.D. and Kuar, S. (eds). 2019. Gender and the Changing Face of Higher Education in Asia Pacific. London: Palgrave Macmillan.